Ergonomic chair intervention: Effect on chronic upper quadrant dysfunction, disability and productivity in female computer workers - C. Hoeben; Q. Louw (AOSIS, 2014)
AIM: To compare the effect of two ergonomic chairs on upper quadrant musculoskeletal pain and tension, disability and productivity among female computer workers in the office workplace.METHODS: A series of two N=1 studies were conducted using the A-B-A-C-A design whereby an intervention ergonomic chair was compared to a less adjustable control ergonomic chair using visual analogue scales (VAS) for pain and muscle spasm, the Neck Disability Index and the Work Productivity and Activity Impairment questionnaire. The female participants were assessed over the four week phases as they performed high intensity visual display unit work. The results were compiled and tabulated.RESULTS: Both the control and intervention ergonomic chairs showed a reduction in both the mean and variance of pain and muscle spasm. The second participant also showed an increase in productivity with both chairs.CONCLUSION: The introduction of an ergonomic chair shows a reduction in VAS intensity and frequency for pain and muscle spasm, as well as a reduction in variance of the symptoms. Both chairs showed a similar reduction in symptoms, thus indicating almost equivalent benefit from the use of both ergonomic chairs.